Requestioning Pregnant Women Again Out of Wedlock in Bugis Community in the Modern Era: Perspective of Human Rights and Islamic Law - Hannani Hannani (LPPM IAIN Parepare, 2021)
This study aims to discuss the issue of pregnant women out of wedlock in Bugis community in the modern era in relation to the shift in the value of customary sanctions from the perspective of human rights and Islamic law. This study consists of two problems, namely the application of customary sanctions against women who are pregnant out of wedlock and the shift in the value of customary sanctions against women who are pregnant out of wedlock in the modern era from the perspective of human rights and Islamic law. The research methodology was carried out using a qualitative-descriptive field research approach. Data collection by way of observation, interviews, documentation. Sources of data are from the Bugis community, both academics and traditional leaders. Data processing is carried out with data related to the study and data analysis carried out by the theory of legal change and the theory of human rights. The results of the study show that 1) The application of customary sanctions against pregnant women out of wedlock in Bugis community is seen as a disgrace and shame so that customary sanctions called dipaoppangi tana apply, namely women are considered dead and the lineage from their family is erased, unless men are willing marrying a woman who causes her to become pregnant, or it can be with another man who is commonly known as pattongko siri, and 2) Traditional sanctions against women who become pregnant out of wedlock have experienced a shift in values both in the system of norms after being studied in Islamic law and human rights.